COVID-19 Pandemic: Awakening the Call for Paradigm Shifting in the Teaching, Learning, Research and Professional Development: In Human and Peoples’ Rights, Freedoms and Responsibilities in Africa - Gutto, Shadrack B.O (Strathmore Law Journal, 2021)
The COVID-19 pandemic has awoken the entire world from its slumber – the highly-industrialised and the less-industrialised, those regarded to be developed and the less developed or underdeveloped in sciences and technologies, the rich/wealthy and the poor-but-rich-in-resources alike. It has shown that it has no respect for the few who belong to the ruling class and political elites – the virus’ attack on the heir-to-the-throne in Britain, Prince Charles, and the British Prime Minister, Boris Johnson, are good examples. International conferences and summits of heads of state and governments are being conducted virtually. Educators and students from primary school to university and college levels are forced to re-skill to teach and learn online and not mainly through contact learning as was the established norm. Contextually, limited electrification hinders access to the internet and digitisation. The emerging norm is no longer going to be the traditional separation of the sciences, technology, engineering and medicine (STEM) from humanities and social sciences. The interface and interrelatedness of disciplines is a requirement in managing and manoeuvring human life through this pandemic, and beyond. There should be more use of multi-discipline and inter-discipline perspectives and approaches of knowledge development and application. This is not a call for the death of mono-disciplines. They remain essential fields of specialisation within broader contexts.